2016
DOI: 10.1007/s00289-016-1698-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel biosensor based on electro-co-deposition of sodium alginate-Fe3O4-graphene composite on the carbon ionic liquid electrode for the direct electrochemistry and electrocatalysis of myoglobin

Abstract: A novel biosensor based on electro-co-deposition of myoglobin (Mb), sodium alginate (SA), Fe 3 O 4 -graphene (Fe 3 O 4 -GR) composite on the carbon ionic liquid electrode (CILE) was fabricated using Nafion as the film forming material to improve the stability of protein immobilized on the electrode surface, and the modified electrode was abbreviated as Nafion/Mb-SA-Fe 3 O 4 -GR/CILE. FT-IR and UV-vis absorption spectra suggested that Mb could retain its native structure after being immobilized in the SA-Fe 3 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Superior sensitivity and specificity of electrochemical sensors can only be achieved when there are well-covered recognition molecules or labels as bridges for electron transfer between electrodes and target molecules. Up to the present date, redox proteins such as hemoglobin (Hb) (Figure a) , ,, , ,, and myoglobin (Mb), ,,,, , metal complexes including porphyrin (Figure b), enzymes like horseradish peroxidase (HRP) , and phthalocyanine, and molecular imprinted polymers (MIPs) , (Figure c) have been applied as recognition molecules for electrochemical determination of various DBPs in water. From Table (28 out of 40 references), the application of redox proteins was particularly dominant as compared with other recognition mechanisms.…”
Section: Dbps Detection Using Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superior sensitivity and specificity of electrochemical sensors can only be achieved when there are well-covered recognition molecules or labels as bridges for electron transfer between electrodes and target molecules. Up to the present date, redox proteins such as hemoglobin (Hb) (Figure a) , ,, , ,, and myoglobin (Mb), ,,,, , metal complexes including porphyrin (Figure b), enzymes like horseradish peroxidase (HRP) , and phthalocyanine, and molecular imprinted polymers (MIPs) , (Figure c) have been applied as recognition molecules for electrochemical determination of various DBPs in water. From Table (28 out of 40 references), the application of redox proteins was particularly dominant as compared with other recognition mechanisms.…”
Section: Dbps Detection Using Electrochemical Biosensorsmentioning
confidence: 99%
“…To prevent recognition molecules (e.g., redox proteins and enzymes) from damage and leakage during the sensor fabrication process, many film-forming agents including chitosan ,,, ,, and Nafion ,,,,,,,, , were utilized to form a durable electrochemical sensing matrix. The activity of biomolecules was maintained due to the presence of microenvironments built by these film-forming agents .…”
Section: Dbps Detection Using Electrochemical Biosensorsmentioning
confidence: 99%
“…Kim and Wang et al 16,17 have reported a kind of SA-polydiallyldimethylammonium chloride hydrogel that is able to produce large deflection in 0.6 wt% HCl solution and is positively correlated with the applied voltage. Chen et al 18 has proposed a new bioactuator based on the electrodeposition of myosin, SA and Fe 3 O 4 -graphene complex on carbon ionic liquid electrode, which possesses good electrocatalytic performance for the reduction of trichloroacetic acid, and can be used as a potential bioactuator platform in electrical analysis and electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Nafion has been reported [38] to act as a conductive matrix, with which salicylaldehyde azine and MWCNTs could be strongly fixed onto the electrode surface for the selective determination of Cu 2 + . Thus, rich of hydrophilic groups with strong polarity and electronegativity (e. g., sulfo-groups, À SO 3 H) [39], provided to be used together with CMC, Nafion probably can (i) adsorb metal cations through both electrostatic attractions and coordination bonds (behave like CMC) [40][41], so as to improve the sensitivity and selectivity of CMC-based electrode; (ii) form strong hydrogen bonds with water molecules (compete with CMC) [42], so as to change the hygroscopicity of CMC and improve the sensing stability; (iii) form a natural barrier to prevent negative-charged particles from aggregating [43][44], herein to prevent the stacking of CMC layers, which will be favourable for the improvement of the sensing performance; (iv) directly form a composite membrane with CMC for the same good film-forming ability [45], so as to further improve the sensing performance. In a word, theoretically, Nafion seems to be a promising candidate from multiple perspectives for the improvement of the stability and sensitivity of CMC-based electrode.…”
Section: Introductionmentioning
confidence: 99%